Democratization and the secularization of religious parties: the case of Mexico. Issue 3 (15th April 2016) - Mantilla, Luis Felipe
Abstract : Under what conditions does democratization erode religious political engagement? The dramatic democratic transitions in the Catholic world during the last quarter of the twentieth century have been accompanied by the widespread decline of Catholic political parties, but the interaction between democratizing reforms and the development of religious parties in the Catholic world remains poorly understood. This article analyses the crucial case of Mexico to explore if, how, and under what conditions electoral participation encourages the differentiation of religious and partisan activism. Relying on archival research and an original data set describing the religious linkages of 302 historic and contemporary leading members of the PAN, Mexico's largest Catholic-inspired party, this article shows that democratization is only indirectly linked to the secularization of religious parties, and its effects are conditional on the resources and opportunities available to religious activists.